Ecotoxicologia do glifosato e surfactante aterbane® br para guaru (Phalloceros caudimaculatus) - Shiogiri, Natália Sayuri [UNESP] (2010)
Aquatic macrophytes are important components of aquatic ecosystems, but these plants have become a problem due to their occurrence in different regions. Some studies aimed to demonstrate the effectiveness of herbicides to control these macrophytes; however, few studies report the possible ecotoxicological effects. The objective of this study was to estimate the acute toxicity (LC (I)50;96h) and assess water quality variables for glyphosate in the Rodeo® formulation, Aterbane® BR surfactant and mixtures of glyphosate + 0.5% and 1.0% of surfactant, for the guaru fish (Phallocerus caudimaculatus). The guaru was exposed to increasing concentrations of glyphosate and a mixture of glyphosate + 0.5 and 1.0% of surfactant. The mixture of glyphosate and glyphosate + 0.5 and 1.0% of surfactant showed (LC (I)50;96h) > 975.0 mg L -1. For the surfactant, the rate was 5.81 mg L -1. The glyphosate and mixtures of glyphosate + 0.5% and 1.0% of surfactant caused a decrease in pH and dissolved oxygen and increased the electrical conductivity of water. Glyphosate in the Rodeo® formulation and the mixtures with surfactant Aterbane® BR can be classified as practically nontoxic, whereas surfactant Aterbane® BR can be considered as moderately toxic to guaru.